Design and application of a novel 3D printing digital navigation template for cubitus varus deformity in children - Ming Zou; Youzhi He; Yuxia Xu; Qiang Shi; Hao Zeng (Frontiers Media S.A., 2024)
BackgroundThis study was aimed to assess the feasibility and efficacy of 3D printing digital template for treatment of cubitus varus deformity.Methods32 patients who underwent lateral closing osteotomy were evaluated between January 2018 and January 2020 in this retrospective study. Navigation templates were used in 17 cases, while conventional surgery in 15 cases. The carrying angles before and after surgery, operation time and elbow joint function were compared.ResultsNavigation templates matched well with the anatomical markers of the lateral humerus. More accurate osteotomy degrees, shorter operation time and less radiation exposure were achieved in the navigation template group (p < 0.05). At the last follow-up time, significant difference was found based on the Bellemore criteria (p = 0.0288).ConclusionsThe novel navigation template can shorten operation time, improve the lateral closing osteotomy accuracy and improve postoperative elbow joint function.